An Electron Transporting Blue Emitter for OLED - Qi, Boyuan; Luo, Jiaxiu; Li, Suyue; Xiao, Lixin; Sun, Wenfang; Chen, Zhijian; Qu, Bo; Qihuang Gong (LED AND DISPLAY TECHNOLOGIES, 2010)
After the premier commercialization of OLED in 1997, OLED has been considered as the candidate for the next generation of flat panel display. In comparison to liquid crystal display (LCD) and plasma display panel (PDP), OLED exhibits promising merits for display, e. g., flexible, printable, micro-buildable and multiple designable. Although many efforts have been made on electroluminescent (EL) materials and devices, obtaining highly efficient and pure blue light is still a great challenge. In order to improve the emission efficiency and purity of the blue emission, a new bipolar blue light emitter, 2,7-di(2,2': 6', 2 `'-terpyridine)- 2,7-diethynyl-9,9-dioctyl-9H-fluorene (TPEF), was designed and synthesized. A blue OLED was obtained with the configuration of ITO/PEDOT/PVK:CBP:TPEF/LiF/Al. The device exhibits a turn-on voltage of 9 V and a maximum brightness of 12 cd/m(2) at 15 V. The device gives a deep blue emission located at 420 nm with the Commission Internationale de l'Eclairage (CIE) coordinates of (0.17, 0.10). We also use TPEF as electron transporting material in the device of ITO/PPV/TPEF/LiF/Al, the turn-on voltage is 3 V. It is proved the current in the device was enhanced indeed by using the new material.